Presence of Atrial Fibrillation in Stroke Patients With Patent Foramen Ovale: Systematic Review and Meta-Analysis - Chen, Jessie Ze-Jun; Thijs, Vincent N. (Frontiers in Neurology, 2021)
Purpose Patent foramen ovale (PFO) is associated with ischaemic stroke, especially in patients with embolic stroke of undetermined source. This study aims to evaluate the presence of atrial fibrillation (AF) in ischaemic stroke patients with PFO. Methods We systematically searched EMBASE and MEDLINE databases on 21st May, 2020 for studies that analysed the presence of atrial fibrillation in patients with PFO. The primary outcome was the presence of AF in patients with PFO compared to those without. Outcomes were pooled using a random-effects model using the method of DerSimonian &Laird. We recorded demographic characteristics and the methods used for AF detection in included studies (unspecified, history/medical records review, ECG, Holter monitor, or loop recorder). Results A total of 14 studies and 13,245 patients fulfilled entry criteria. The average age was 61.2 years and 41.3% of the participants were female. There was a lower risk of AF detection in patients with PFO compared to those without (RR 0.52, 95% confidence interval, 0.41-0.63, p<0.001). There was no evidence of heterogeneity. The lower detection of AF was found in cross-sectional and longitudinal studies and in studies stratified by average age (<60 or >=60) and in cryptogenic stroke. Meta-regression by PFO detection technique suggested that studies using transoesophageal echocardiogram for PFO detection reported higher risk of AF (1.39, 95% confidence interval 1.14-1.70, p=0.004). Conclusion Diagnosis of a PFO in patients with ischaemic stroke/TIA may be associated with a lower presence of AF. Few comparative studies have estimated the risk of future AF in patients with PFO.